Brunner Gland Hamartomas-Uncommon Presentations and Endoscopic Management - Ali Khalifa MD; Yi-Chia Wu MD; Sugirdhana Velpari MD; Andrew Korman MD (SAGE Publishing, 2023)
Brunner gland hamartoma (BGH) is a rare condition that requires a high clinical suspicion to diagnose. Large hamartomas may initially present with iron deficiency anemia (IDA) or symptoms suggesting intestinal obstruction. Barium swallow may demonstrate the lesion, but endoscopic evaluation is the acceptable first line management unless a concern for underlying malignancy. The present case report and literature review highlight the uncommon presentations and endoscopic role in large BGHs management. Internists should consider BGH in their differential, especially in patient with occult bleeding, IDA, or obstruction, which can be treated with endoscopic resection of large sized tumors by trained experts.